It is suggested that…or it is better to…? Forms and meanings of subject it-extraposition in academic and popular writing - Zhang, Guiping (Journal of English for academic purposes, 2015)
Research has shown that extraposition is more frequent in academic writing than in speech and that students and non-English speaking academic writers have problems with the use of extraposition. With the explosion of scientific popularization over the past decades, popular writing has also become an important register in English for academic purposes. However, few studies have been devoted to comparing the use of extraposition in academic and popular writing. This study attempts to reveal how subject it-extraposition is used in the two registers based on an analysis of the extraposed subjects in the academic and popular writing subcorpora in the British component of the International Corpus of English (ICE-GB). Differences are identified between the two registers in both the forms and meanings of subject it-extraposition. Results show that, in academic writing, passive verbs are more frequent in the main clauses of extraposed sentences, and the most common extraposed clause is that-clause rather than to-clauses. Semantically, academic writing is more concerned with explanation and negotiation rather than evaluation. The results of this study can be used in designing activities in EAP to raise students' consciousness of register variations in the use of subject it-extraposition and help students to grasp this construction. •Compares the use of subject it-extraposition in academic and popular writing.•Classifies the types of clauses extraposed in the two registers.•Analyzes the forms and meanings of the matrix predicates in the extraposition.•Identifies differences in the extraposition used in the two registers.•Reveals interaction between the forms and meanings of the extraposition.